The Future of US Global Power - Brown, S. author. aut Link
X, 321 p.
Keywords: Dispelling the myth of decline, Stuart Brown argues that the US continues to enjoy the economic, political, cultural and military underpinnings befitting a pre-eminent global power. He provides an analytical tour through the major domestic and foreign policy issues that will impact the United States' future position and role in the global system.